Preservation of the collagen structure by coaxial electrospinning method - Yavuzsoy, Efe Cuma. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2021., 2021)
Collagen is one of the most important material for biomedical technologies. Both its biological and mechanical properties enable collagen to be used in many fields such as biomaterials, tissue engineering etc. The use of collagen in the production of electrospun nanofibers reveals promising results for both research and clinical based areas such as tissue scaffolding. However, collagen can lose its natural structure by being affected by many parameters during the formation of nanofibers with desired physical properties. In this thesis, coating of collagen nanofibers with a biodegradable polymer, Poly Vinyl Alcohol (PVA), using coaxial electrospinning method is demonstrated. It was hypothesized that the structure could be protected by coating the collagen nanofibers with PVA. Thermal and spectroscopic analyzes show that collagen and PVA are present in the obtained nanofiber structures. With optical and scanning electron microscope images, the difference between the fibers produced by the coaxial electrospinning system and those produced by the conventional electrospinning system was demonstrated. This work is considered as a preliminary study, it is hypothesized that the nanofibers to be produced by the coaxial electrospinning method as used in this thesis may show biological activity-enhancing properties in vivo and in vitro experiments as tissue scaffolds in future research.|Keywords : Coaxial Electrospinning, Collagen Nanofibers, Collagen Tissue Scaffold, PVA
Keywords: Electrospinning.; Collagen.; Polyvinyl alcohol.